1985
DOI: 10.1002/cber.19851180626
|View full text |Cite
|
Sign up to set email alerts
|

Carben‐Reaktionen, XVIII. Thermisches Verhalten von 7‐Alkylidenbicyclo[2.2.1]heptadien‐Derivaten

Abstract: 7-Alkylidennorbornadiene 2 werden thermisch in einem Retro-Diels-Alder-Zerfall in ein Fulven und Acetylen gespalten. Ein abweichendes Verhalten -Spaltung in Benzol und ein Carbenfindet man bei solchen Derivaten von 2, die an C-8 eine 0 -oder x-Donor-Funktion besitzen. Die Abhangigkeit der Reaktionswege von der Natur der Substituenten an C-8 wird auf der Basis von MO-Uberlegungen diskutiert.Carbene Reactions, XVIII ' ) Thermal Behaviour of 7-Alkylidenebicyclo[2.2.llheptadiene Derivatives Thermolysis of 7-alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The synthesis is partially based on the work by Butler et al 17. and Hoffmann et al 18. Here we synthesize quadricyclanone 8 in gram quantities starting from norbornadiene in an overall yield of 5 % over five steps.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis is partially based on the work by Butler et al 17. and Hoffmann et al 18. Here we synthesize quadricyclanone 8 in gram quantities starting from norbornadiene in an overall yield of 5 % over five steps.…”
Section: Introductionmentioning
confidence: 99%
“…[102] Shortly thereafter Prinzbach reported almost quantitative isomerisation of tricyclic fulvene 64 into 6 by Ag I catalysis (90 %) and upon photolysis (97 %), [117] while Hoffmann et al demonstrated that the norbornadiene 56d (R 1 = R 2 = R 3 = H) also gave 6 among a range of products from thermolysis at 500°C. [118] Much more recently, Li and Neuenschwander [119] have provided a potentially new general pathway to 6 (and heptafulvene and heptafulvalene 7) that currently terminates at 65 (Scheme 13). A detailed experimental examination of the dehydrobromination of 65 is still needed to complete the sequence for which it must be noted that trisdehydrobromination of the precursor yields 3-bromocyclopropabenzene (Scheme 13).…”
Section: Pentaheptafulvalenes (Sesquifulvalenes)mentioning
confidence: 98%
“…Generally, VDCPs 1 are prepared through the reaction of alkenes with in situ produced alkenylidenecarbenes . These alkenylidenecarbenes can be formed by treating halogenoalkynes, halogenoallenes, ,,, polyhalogenocyclopropanes, and polyhalogenoalkanes with strong bases, which can also be generated by heating of diazoallenes and so on .…”
Section: Preparation Of Vdcpsmentioning
confidence: 99%